2019
DOI: 10.3390/rs11232855
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Estimation for Semiarid Vegetation and Mine Rehabilitation Using Worldview-3 and Sentinel-1 SAR Imagery

Abstract: The surface mining activities in grassland and rangeland zones directly affect the livestock production, forage quality, and regional grassland resources. Mine rehabilitation is necessary for accelerating the recovery of the grassland ecosystem. In this work, we investigate the integration of data obtained via a synthetic aperture radar (Sentinel-1 SAR) with data obtained by optical remote sensing (Worldview-3, WV-3) in order to monitor the conditions of a vegetation area rehabilitated after coal mining in Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“…The observed moderate relationships of independent variables of the RS data with AGB demonstrated the potential of optical RS data for developing models to enhance AGB estimation. The observed negative correlation coefficients between the mean of SB reflectance and AGB agree with results of similar studies conducted in various forest types [19,75,76]. The negative correlation coefficients indicate the inverse relationship between reflectance values from the SBs and AGB.…”
Section: Variable Exploration For Estimating Agb and Model Selectionsupporting
confidence: 89%
“…The observed moderate relationships of independent variables of the RS data with AGB demonstrated the potential of optical RS data for developing models to enhance AGB estimation. The observed negative correlation coefficients between the mean of SB reflectance and AGB agree with results of similar studies conducted in various forest types [19,75,76]. The negative correlation coefficients indicate the inverse relationship between reflectance values from the SBs and AGB.…”
Section: Variable Exploration For Estimating Agb and Model Selectionsupporting
confidence: 89%
“…Considerable researches have been conducted to estimate various crop parameters using satellite Earth observations, including RADARSAT-2 [1,17,[19][20][21], RapidEye [5,19,20,22,23], Sentinel-1 [7,17,[24][25][26][27][28], Sentinel-2 [7,25,[29][30][31][32], Landsat-5 Thematic Mapper (TM) [33,34], Landsat-7 Enhanced Thematic Mapper Plus (ETM+) [34][35][36], Landsat-8 Operational Land Imager (OLI) [7,17,31,32,[35][36][37], Worldview-2/3 [17,27,28,38,39], and MODIS [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the use of passive optical sensors, active sensors demonstrate the capacity for ecological monitoring of rehabilitation but are still relatively under-utilized. Bao et al (2019) found that fusing WorldView-3 optical bands with Sentinel-1 SAR bands increased the correlation with on-ground measurements of above ground biomass and resulted in a model with a higher prediction accuracy (r 2 = 0.79, RMSE = 22.82gm −2 ) compared to WorldView-3 and Sentinel SAR, separately in a rehabilitated semi-arid grassland in North China [24]. Other studies showed improvement in accuracy by including auxiliary non-spectral light detection and ranging (LiDAR) data.…”
Section: Chronological Development Of Remote Sensing For Mapping Rehabilitationmentioning
confidence: 99%
“…However, remote sensing assessments of mine site rehabilitation require considerable knowledge and skill to interpret outputs of analysis and derive meaningful results. This is highlighted by a number of studies emphasizing the heterogeneous nature of mine site rehabilitation and the unique spatial and temporal challenges for remote sensing assessments [21][22][23][24][25][26][27][28][29][30]. Alternatively, the distinctive spectral, temporal and spatial patterns of rehabilitated landscapes provides opportunities for remote sensing to derive valuable ecological information.…”
Section: Recommendations For Operationalising Remote Sensing For Mine Site Rehabilitationmentioning
confidence: 99%
See 1 more Smart Citation